Decentralisation policy in the incremental process of institutional capacity building of responsibility centers / Zanariah Mohd Nor ... [et al.] - Mohd Nor, Zanariah; Suandi, Turiman; Md. Sail, Rahim; Hamzah, Azimi (2002)
Decentralisation policy bears the concept of empowerment as a recourse to overcome some limitations of a centralised system. The policy was implemented in a public university in 1995 and yet, after five years of its commencement, several problems emerged. This envisaged that the policy did not seem to achieve its objectives. The study was an attempt to identify the constraints faced by Responsibility Centers (RCs) in administering and managing academic and support functions under the decentralised policy. The model of public policy, administration and finance by Rondinelli et al. (1989; 1984) was employed to guide the study. Semi-structured interviews were conducted with 16 informants and Ethnograph ver 5 was used to analyse the data. Under the decentralised system, the study revealed that the RCs encountered several constraints related to bureaucratic, organisational and resource factors. The central authority has assigned insufficient empowerment to RCs incommensurate with the increased workload and responsibilities under the system. The problem was aggravated by inadequate documentation on policy, regulations, procedures and strategies to guide RCs in operating as decentralised entities. The central authority seemed unable to provide adequate and necessary resources to support RCs' operations. Despite problems and constraints faced, the study showed that, to some extent, the empowerment developed viability among RCs to seize opportunities in mitigating the contraints. The decentralised policy, thus, had potentials to enhance the institutional capacity building of university governance. There is a need for the university to review the factors related to bureaucratic, organisational and resources to ensure that the policy would achieve its objective and to support the RCs to function as decentralised entities. The central authority should strongly support and give full commitment in empowering the RCs adequately. Sufficient policy documents with concepts and principles of decentralisation should be in place as an effective monitoring system, and provision of adequate resources to RCs is needed to support operations.